The Mystery of Name as the Fate of Essence Itself (based on V.K. Kyukhelbecker's novel The Last Kolonna) (Филологический класс, 2012)
The contributor focuses on the image of the romantic hero, J. Kolonna, who took on the ancient name of Carthege conqueror. From the point of view of sign history, symbol, myth and name in their dialectic unity developed by A.F. Losev the choice of a fateful name is one of the chief motives of personality formation and self-identification. Hence the disruptive energy contained by the name Kolonna proves to be extremely important.